The Role and Participation of Family Welfare Empowerment Cadres (PKK) in Stunting Prevention: A Case Study in Bojonegoro - Ningtias, Ika Sylvia; Kustanti, Asihing; Sukesi, Keppi (Universitas Pendidikan Ganesha, 2024)
Stunting which is a condition of chronic malnutrition since 1000 days of a child's life is still a health problem in Indonesia, ranked second in the world. Empowerment of health cadres is one of the efforts made by the government in improving the nutritional health of toddlers. This study underscores the urgency of understanding the role and participation of Family Welfare Empowerment (PKK) cadres in stunting prevention. The purpose of the study was to analyze the role and level of participation of PKK cadres in implementing stunting prevention programs. The research method included qualitative research with a case study type, using in-depth interviews and observations of PKK cadres as data collection techniques. While the data analysis technique was carried out descriptively using interactive analysis techniques. The results showed that PKK cadres serve as important mediators in disseminating nutrition and health information, as well as facilitating community access to health services. The implications of these findings highlight the importance of empowering PKK cadres as an effective strategy in combating stunting, and emphasize their vital role in supporting child health and sustainable community development.